Educational aspects in the development of multicultural tourism: A multisite study on Pura Lingsar and Makam Batu Dendeng - Harnika, Ni Nyoman; Sendra, I Made; Putra, I Nyoman Darma; Kristanto, Yohanes (Edelweiss Applied Science and Technology, 2025)
This study aims to explain the relationship between education and the development of multicultural tourism in Pura Lingsar and Makam Batu Dendeng. Tourism development often marginalizes the role of education, but in fact, optimal education plays a very important role in the process of tourism development based on multiculturalism. The study adapts qualitative research with multisite studies. The data was obtained using observation and interviews; in addition, the Miles, Huberman, and Saldana model was used as a data analysis technique and integrated with triangulation techniques to obtain valid data. Based on the results of data analysis, the educational aspect in the development of multicultural-based tourism in Pura Lingsar and Makam Batu Dendeng consists of two scopes. First, education is an effort to preserve tradition and culture so that tourism does not become a destructive element that eliminates cultural identity. Second, education supports the strengthening and development of multicultural-based tourism for the economic progress of the community around Pura Lingsar and Makam Batu Dendeng, especially related to improving human resources. It can serve as a literature review on the importance of the educational aspect in tourism development.